2018
DOI: 10.1108/qaoa-01-2018-0003
|View full text |Cite
|
Sign up to set email alerts
|

The importance of a room with a view for older people with limited mobility

Abstract: This paper examines how older people who are almost entirely housebound use a view from their window to make sense of the world and stay connected to the outside space that they cannot physically inhabit. • Design/methodology/approach (mandatory) Semi-structured interviews with 42 individuals were carried out who were living at home, were relatively immobile and had an interesting view outside they liked from one or more of their windows. • Findings (mandatory). The findings suggest immobile older people enjoy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 31 publications
2
24
0
Order By: Relevance
“…Many of the people we spoke to commented on how it felt when a quiet atmosphere descended upon their local area, sometimes as a result of being left behind when others went off to work or school during the day. Other studies have found that windows were sources for informal interactions and a sense of belonging by getting a smile through the window for older people with limited mobility (May and Muir, 2015;Musselwhite, 2018) and for people living with dementia (Ward et al, 2018). Just to hear voices or see children playing outside gave hope and a sense of connection, especially for the women to whom we spoke.…”
Section: Discussionmentioning
confidence: 86%
“…Many of the people we spoke to commented on how it felt when a quiet atmosphere descended upon their local area, sometimes as a result of being left behind when others went off to work or school during the day. Other studies have found that windows were sources for informal interactions and a sense of belonging by getting a smile through the window for older people with limited mobility (May and Muir, 2015;Musselwhite, 2018) and for people living with dementia (Ward et al, 2018). Just to hear voices or see children playing outside gave hope and a sense of connection, especially for the women to whom we spoke.…”
Section: Discussionmentioning
confidence: 86%
“…For example, it has been reported that in clinical settings, viewing natural scenery (e.g., ornamental indoor plants or a bedside window view of trees) can reduce hospital length-of-stay and reduce the use of pharmaceuticals (18,19,22,23). It has also been shown that housebound older adults often use a view from their window to stay connected to the outside space that they cannot physically explore (24). Therefore, it would be highly advantageous to identify novel methods of providing older adults with new experiences and exposure to natural scenes, while accounting for barriers to mobility and autonomy as well as concerns for safety.…”
Section: Introductionmentioning
confidence: 99%
“…The visual link of observing the neighbourhood (from the balcony and/or window) in the moment created a sense of belonging to the lived neighbourhood where life and movement were ongoing (study II). A body of research aligns with these findings and has also shown that windows were resources that upheld a sense of belonging to the wider world outside, for example, by getting a smile through the window for older people (Coleman & Kearns, 2015;May & Muir, 2015;Musselwhite, 2018) and for people living with dementia (Ward et al, 2018). To see other people moving and interact with them creates meaning, especially for people living with dementia (Ashworth, 2006).…”
Section: Walkable Attachment To the Lived Neighbourhoodmentioning
confidence: 83%